Pengaruh Pemanfaatan Teknologi Informasi, Whistleblowing System, dan Peran Audit Investigatif Terhadap Pengungkapan Fraud - Imas Mutikartini Putri; Marta Marta; Nera Marinda Machdar (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
The study looked at three different ways to uncover fraud: using advanced technology, providing secure reporting channels, and providing an investigative audit role. Technology helps detect fraud by offering robust information systems. According to this study, which was conducted through in-depth analytical methods, technology and reporting systems increase the effectiveness of investigative audits to discover fraud.